Surface morphology and crystal growth mechanism of gibbsite in industrial Bayer liquors - Parkinson, Gordon; Freij, Sawsan (Elsevier Science BV, 2005)
Atomic force and scanning electron microscopy have been used to study the surface topography and crystal growth mechanism of gibbsite crystals in inducstrial Bayer liquors. AFM images of the as-grown basal face of industrially produced gibbsite show that the surface is rough and contains diamond shaped features, whereas freshly cleaved basal planes show steps of one unit cell height. An array of steps terminating within teh crystal was imaged, indicating the presence of an emergent screw dislocatin. Typical AFM images of the prismatic faces contain molecular steps parallel to the basal face.Growth on single faces of synthetic crystals has been observed by a series of ex situ growth experiments in both industrial (impure) and pure synthetic liquor at constant supersaturation and temperature. The results reveal that growth in plant liquor is almost inhibited on the prismatic faces, while futher immersion in pure solution induces growth by formation of prism-shaped muclei. This may suggest that organics from plant liquor adsorb stronly to the growth sites on teh prismatic faces, preventing the incorporation of the growth units, and further growth in pure solution occurs by nucleation and spreading of surface features.Growth on the basal faces of gibbsite in plant liquor occurs by a birth and spread mechanism, which may suggest that the interation of process liquor organics within process liquor with the basal face is different than their interaction with the prismatic faces.